AYAM JANTAN DALAM KARYA SENI GRAFIS - M. SYARIF ARBI, Drs. Irwan, M. Sn., Drs. Abd. Hafiz, M.Pd (Universitas Negeri Padang, 2019)
The purpose of lifting this final work is to visualize the behavior of chickens that have similarities with human behavior, also inform the public about the behavior of chickens with human behavior. The method of creating this work uses five stages: Preparation (tools and materials), elaboration stage, censensis, realization of concepts, completion, and this work uses a relief print technique. The visual form of the work is packed with the title: Morning Crowding, Flapping Wings, Pair, Jealousy, Waiting, Looking for Worms Behind Stones, Dividing Food, Protecting, Fighting, Fighting, the Hero.Keywords: Chicken Behavior, Human Behavior, Graphic Arts.